2020
DOI: 10.2196/18226
|View full text |Cite
|
Sign up to set email alerts
|

A One-Step, Streamlined Children’s Vision Screening Solution Based on Smartphone Imaging for Resource-Limited Areas: Design and Preliminary Field Evaluation

Abstract: Background Young children’s vision screening, as part of a preventative health care service, produces great value for developing regions. Besides yielding a high return on investment from forestalling surgeries using a low-cost intervention at a young age, it improves school performance and thus boosts future labor force quality. Leveraging low-skilled health care workers with smartphones and automated diagnosis to offer such programs can be a scalable model in resource-limited areas. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…evaluated a new photo screening solution with a smartphone-based automated Hirschberg test and photorefraction powered by DL and image-processing algorithms and it showed that the sensitivity and specificity were both high in strabismus, myopia and anisometropia detection. 29 Combining principles of mobile screening and DL, Murali et al. built a simple photography-based system (Kanna) to help detect amblyopia based on the amblyogenic risk factors (ARF).…”
Section: Resultsmentioning
confidence: 99%
“…evaluated a new photo screening solution with a smartphone-based automated Hirschberg test and photorefraction powered by DL and image-processing algorithms and it showed that the sensitivity and specificity were both high in strabismus, myopia and anisometropia detection. 29 Combining principles of mobile screening and DL, Murali et al. built a simple photography-based system (Kanna) to help detect amblyopia based on the amblyogenic risk factors (ARF).…”
Section: Resultsmentioning
confidence: 99%
“…Yang et al [16] have developed a deep learning (DL) model to evaluate whether teenagers are myopia through eye surface images, and the area under the receiver operating characteristic (ROC) curve reached more than 80%, realizing the remote monitoring of refractive status. Ma et al [17] developed an application based on a DL algorithm that can automatically measure pupil distance, dioptre range, and other data in a dark room by using a smart-phone. Combined with personal information, it can calculate the risk of schoolchildren developing strabismus, myopia, and anisometropia.…”
Section: Discussionmentioning
confidence: 99%
“…Instrument-based devices using technology based on visual evoked potentials, retinal birefringence, and eye-tracking technologies are currently in development and may provide additional means to assess visual acuity and ocular health in young children [ 26 , 44 ]. Smartphone applications can expand access to vision screenings, especially in areas with limited access to traditional vision screening programs [ 45 , 46 ].…”
Section: Part 2: Future Directions and Priority Areas For Vision Scre...mentioning
confidence: 99%